Is Public Debt Asymmetrically Link to Financial Development in Malaysia? - Chung-Yee, Liew; Ismail, Normaz Wana; Ai-Lian , Tan (Asian Journal of Empirical Research, 2020)
This study investigates the asymmetric effects of public debt on financial development in Malaysia. Employing time series data for the period of 1980-2015 and nonlinear Autoregressive Distributed Lags framework, this study found that public debt levels are significantly linked to financial development in both short-run and long-run. The findings also conclude the existence of asymmetry effects between public debt and the financial development, and higher debt levels discourage financial development. Domestic lenders are major financier of the public debt and if government continue to incur large borrowing domestically, it would likely to crowd-out private sector because of first, it is reducing the availability of credit to private sector; second, banks may prefer to provide credit to government over private sector due to lower risk premium; and third, leads to more expensive borrowing to private sector due to increasing demand for credit from the public sector.